Axial compressive behaviors of reinforced concrete composite column with precast ultra-high performance concrete (UHPC) jacket. (1st May 2022) - Zhang, Xiaochen; Wu, Xiangguo; Zhang, Dong; Huang, Qingwei; Chen, Baochun
Abstract: To improve the structural performance of the connection region of prefabricated buildings, a new assembled precast ultra-high performance concrete (UHPC) jacket is used for the joint of precast RC column. Experimental and theoretical studies were carried out on the axial compressive behaviors of the RC composite column with the precast UHPC jacket and bolt connectors. The effects of steel fiber content and thickness of precast UHPC jacket on the axial compressive behaviors were analyzed by evaluating the peak load, elastic stiffness, ductility, toughness index, and energy absorption capacity. A partial composite column with the interface was also investigated to understand the effect of the interface between the composite region and the reinforced concrete region. The results showed that diagonal shear failure was observed for all specimens, and the failure of partial composite column occurred in the RC region even though there was an interface between the composite region and RC region. UHPC jacket could significantly improve the peak load, ductility, and energy absorption capacity of composite column but had little effect on the elastic stiffness and toughness index. UHPC jacket with steel fiber of 3 vol% and thickness of 30 mm performed the best among all the tested specimens. Under sufficient composite confinement, the peak load improved with the increment of confinement index. Further, a semi-empirical model considering the composite confinement of the UHPC jacket and bolt connectors is proposed to predict the peak load of the composite column and validated by the test results. Graphical abstract: Image 1 Highlights: Study on UHPC and concrete composite column under axial compressive load. UHPC jacket improves the axial compressive behaviors of composite columns. A semi-empirical model to predict the peak load of composite column is proposed. A confinement index of no more than 5 is proposed as a design control index.